PELATIHAN MANAJEMEN GIGITAN ULAR DAN SIKAP MAHASISWA TERHADAP ULAR - Ade Suryanda; Ratna Komala; Chairunnisa Chairunnisa (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2020)
Snake bite management is a stage that must be involved in dealing with snake bite problems. Attitude toward snakes is an evaluation or reaction of someone feelings toward snakes. The aim of this research was to know collage student attitude toward snakes and the effect of snake bite management training on collage student attitude toward snakes. The method used for this research was quasi experiment. The precondition test, result showed data distributed normal and homogenous. Data analysis uses gain score and hypothesis testing using the t test. The result of study showed that there was a significant different in the average score of attitude of biology students to animals in the experimental class and control class. This research showed there is an effect of snake bite management training on student attitudes towards snakes.